2009
DOI: 10.5395/jkacd.2009.34.4.324
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of maxillary central incisors restored with various post-and-core applications

Abstract: The purpose of this study was to investigate the effect of rigidity of post core systems on stress distribution by the theoretical technique, finite element stress-analysis method. Three-dimensional finite element models simulating an endodontically treated maxillary central incisor restored with a zirconia ceramic crown were prepared and 1.5 mm ferrule height was provided. Each model contained cortical bone, trabecular bone, periodontal ligament, 4 mm apical root canal filling, and post-and-core. Six combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Displacement for the fiber post was <0.035 mm which was found in the current study came in agreement with the study conducted by Seo et al . [ 11 ] which was 0.034 mm and for the dentin post value was still <0.025 mm.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Displacement for the fiber post was <0.035 mm which was found in the current study came in agreement with the study conducted by Seo et al . [ 11 ] which was 0.034 mm and for the dentin post value was still <0.025 mm.…”
Section: Discussionmentioning
confidence: 92%
“…The risk of the root fracture is influenced by the location of stress at dentin, and stresses located at post/dentin interface may influence the risk of loss of post retention. [ 11 ] Thus, every effort should be made to reduce these stresses, by planning the treatment well and using appropriate materials and verifying the procedure by different investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It means that resistance for distortion and stress distribution are dependent on elastic modulus of materials within the canal (Table 2). 8,23,24) The effect of elastic modulus of posts on fracture strength was evaluated from glass fiber posts and titanium posts. D.T.…”
Section: Basic Researchmentioning
confidence: 99%
“…This result is consistent with previous studies by (Genovese et al 2005 Due to the high modulus of elasticity of the posts, the occlusal loads were transmitted directly to the post and post-dentin interfaces. Stresses located at the post-dentin interface may negatively affect post retention (Fu et al 2010;Seo et al 2009), therefore reducing these stresses is vital to minimize the possibility of displacement of the post. As is clear, shear stresses will contribute to detach the post because they produce relative sliding between post-core and dentin (Genovese et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Even though several studies have analyzed the biomechanical behavior of different post-and-core systems, the restoration of root canal-treated teeth still presents several unresolved aspects, and no consensus has been reached in the literature on the best material or technique to use for this purpose (De Castro Albuquerque et al 2003;Li X et al 2008;Ortega et al 2004). However, because of their favorable performance in decreasing dentin stress during masticatory loads, many authors recommend using posts with a high modulus of elasticity to restore weakened endodontically treated teeth (Asmussen et al 2005; Dejak and Mlotkowski 2011; Durmus and Oyar 2014; Seo et al 2009). Furthermore, numerous in vitro studies showed that teeth restored with high-stiffness post materials have a higher fracture resistance than teeth restored with other post systems (Balkaya and Birdal 2013; Maroulakos et al 2015).…”
Section: Introductionmentioning
confidence: 99%